Role of inflammation in cognitive impairment: results of observational epidemiological studies and clinical trials - Gorelick, Philip B. (Annals of the New York Academy of Sciences, 2010)
Inflammation may be an important mechanism underlying dementia and cognitive decline in the elderly. Inflammation has been implicated in the neuropathological cascade leading to the development of Alzheimer's disease and other common forms of dementia in later life. These observations have led to observational epidemiological study to define the association of systemic and brain inflammatory markers on cognitive impairment and dementia. Furthermore, clinical trials have been carried out to better elucidate the possible role of nonsteroidal anti‐inflammatory drugs (NSAIDs) in the prevention or slowing of progression of Alzheimer's disease. In this review, we discuss the observational epidemiological and clinical trial evidence of the role of inflammation on the occurrence and prevention of dementia or cognitive decline. NSAIDs hold promise to prevent dementia if given in an appropriate time window during the induction phase of dementia and to subjects with apolipoprotein E (APOE) e4 alleles. Also, immunotherapy may prove beneficial.